2023
DOI: 10.1093/inthealth/ihac081
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods evaluation of an integrated training package for skin neglected tropical diseases in Kaduna and Ogun, Nigeria

Abstract: Background The overall burden of neglected tropical diseases (NTDs) affecting the skin is undetermined. Skin conditions are among the top 10 causes of disability worldwide. Affected persons seek treatment at advanced stages of the disease, resulting in morbidity and disability. We developed and evaluated an integrated training intervention for early case detection, referral and management of skin NTDs in two states in Nigeria. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…For example, our finding that people with skin NTDs faced out-of-pocket payments at health facilities, even though Ghana’s NHIS notionally covers treatment of skin diseases (including skin NTDs), reflects systemic problems with the NHIS; only half of Ghana’s population is enrolled in the NHIS, and even for those with a valid subscription, delayed claim payments, frequent facility stock-outs, and unapproved charges result in out-of-pocket expenditure [ 33 ]. Our findings on illness representations and stigma echo other studies from Ghana, which found yaws to be associated with dirty water and witchcraft [ 11 ] and BU to be associated with working, bathing, swimming in or drinking unclean water [ 12 , 34 37 ]; insect bites [ 12 , 34 , 38 ]; “weak blood” in children [ 12 ]; and witchcraft [ 11 , 12 , 17 , 18 , 21 , 25 , 32 ]. A minority of people, including health workers, consistently perceive BU as contagious [ 11 , 12 , 17 , 18 , 21 , 25 , 32 ] and BU-affected individuals commonly experience stigma [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, our finding that people with skin NTDs faced out-of-pocket payments at health facilities, even though Ghana’s NHIS notionally covers treatment of skin diseases (including skin NTDs), reflects systemic problems with the NHIS; only half of Ghana’s population is enrolled in the NHIS, and even for those with a valid subscription, delayed claim payments, frequent facility stock-outs, and unapproved charges result in out-of-pocket expenditure [ 33 ]. Our findings on illness representations and stigma echo other studies from Ghana, which found yaws to be associated with dirty water and witchcraft [ 11 ] and BU to be associated with working, bathing, swimming in or drinking unclean water [ 12 , 34 37 ]; insect bites [ 12 , 34 , 38 ]; “weak blood” in children [ 12 ]; and witchcraft [ 11 , 12 , 17 , 18 , 21 , 25 , 32 ]. A minority of people, including health workers, consistently perceive BU as contagious [ 11 , 12 , 17 , 18 , 21 , 25 , 32 ] and BU-affected individuals commonly experience stigma [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our findings on illness representations and stigma echo other studies from Ghana, which found yaws to be associated with dirty water and witchcraft [ 11 ] and BU to be associated with working, bathing, swimming in or drinking unclean water [ 12 , 34 37 ]; insect bites [ 12 , 34 , 38 ]; “weak blood” in children [ 12 ]; and witchcraft [ 11 , 12 , 17 , 18 , 21 , 25 , 32 ]. A minority of people, including health workers, consistently perceive BU as contagious [ 11 , 12 , 17 , 18 , 21 , 25 , 32 ] and BU-affected individuals commonly experience stigma [ 38 , 39 ]. A recent study we conducted with children and adolescents with yaws and BU in Atwima Mponua and a neighbouring district found that school staff contributed to stigmatising practices affecting children with yaws and BU, mainly because of an overinterpreted fear of contagion, and suggested the need for school-based infection control interventions that are sensitive to social context [ 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…School children in the district with skin NTDs also face substantial social exclusion by peers and staff. While studies have demonstrated that case-finding activities can be integrated across skin NTDs [13][14][15], there is little evidence on how best to integrate health system responses more broadly to build sustainable holistic models of skin care [16,17].…”
Section: Introductionmentioning
confidence: 99%